Haematological and Serum Biochemical response of broiler chicks fed diets containing ginger (zingiber officinale) from different processing methods (2015)
An experiment was conducted with 300 one day old (arbor acre) broilers to assess their haematological and serum biochemical response when fed ad-libitum varying levels of dietary ginger from different processing methods. Ten dietary treatments were formulated such that diet 1 was the basal diet (BD) without ginger, diets 2, 3 and 4 were BD+ sundried ginger at 1, 1.5, 2% inclusion levels respectively, diets 5, 6 and 7 were BD+ air-dried ginger at 1, 1.5 and 2% inclusion levels respectively, diets 8, 9 and 10 were BD+ oven-dried ginger at 1, 1.5 and 2% inclusion level respectively. On day 52 of the experiment, blood samples were collected from the wing vein of the birds for haematological and serum biochemical evaluation. Dietary treatments had no significant differences on haematological parameters, except for the packed cell volume (PCV) and monocytes which were significantly P<0.05 influenced by the dietary treatment. Broilers fed with diet containing sun-dried ginger at 1.5% inclusion level had the highest PCV value and monocyte value. The serum biochemical indices were not significantly P>0.05 affected by the dietary treatments. However, the total cholesterol was reduced across the diets that contained ginger when compared with the control.